Corrosion mechanism of a Ni-based alloy in supercritical water: Impact of surface plastic deformation. (November 2015) - Payet, Mickaël; Marchetti, Loïc; Tabarant, Michel; Chevalier, Jean-Pierre
Highlights: The dissolution of Ni and Fe cations occurs during corrosion of Ni-based alloys in SCW. The nature of the oxide layer depends locally on the alloy microstructure. The corrosion mechanism changes when cold-work increases leading to internal oxidation. Abstract: Ni–Fe–Cr alloys are expected to be a candidate material for the generation IV nuclear reactors that use supercritical water at temperatures up to 600 °C and pressures of 25 MPa. The corrosion resistance of Alloy 690 in these extreme conditions was studied considering the surface finish of the alloy. The oxide scale could suffer from dissolution or from internal oxidation. The presence of a work-hardened zone reveals the competition between the selective oxidation of chromium with respect to the oxidation of nickel and iron. Finally, corrosion mechanisms for Ni based alloys are proposed considering the effects of plastically deformed surfaces and the dissolution.